In Vitro and In Vivo Analysis of Extracellular Vesicle‐Mediated Metastasis Using a Bright, Red‐Shifted Bioluminescent Reporter Protein. Issue 1 (19th January 2022) - Perez, Gloria I.; Broadbent, David; Zarea, Ahmed A.; Dolgikh, Benedikt; Bernard, Matthew P.; Withrow, Alicia; McGill, Amelia; Toomajian, Victoria; Thampy, Lukose K.; Harkema, Jack; Walker, Joel R.; Kirkland, Thomas A.; et al.
Abstract: Cancer cells produce heterogeneous extracellular vesicles (EVs) as mediators of intercellular communication. This study focuses on a novel method to image EV subtypes and their biodistribution in vivo. A red‐shifted bioluminescence resonance energy transfer (BRET) EV reporter is developed, called PalmReNL, which allows for highly sensitive EV tracking in vitro and in vivo. PalmReNL enables the authors to study the common surface molecules across EV subtypes that determine EV organotropism and their functional differences in cancer progression. Regardless of injection routes, whether retro‐orbital or intraperitoneal, PalmReNL positive EVs, isolated from murine mammary carcinoma cells, localized to the lungs. The early appearance of metastatic foci in the lungs of mammary tumor‐bearing mice following multiple intraperitoneal injections of the medium and large EV (m/lEV)‐enriched fraction derived from mammary carcinoma cells is demonstrated. In addition, the results presented here show that tumor cell‐derived m/lEVs act on distant tissues through upregulating LC3 expression within the lung. Abstract : Cancer cell‐derived extracellular vesicles (EVs) promote tumor growth and spread. Studying the distribution of EVs in the body is key to understanding cancer progression and developing therapies. Here, a novel EV reporter for tracking medium and large EVs (m/lEVs) in mice in vivo is developed. Moreover, it is demonstrated that m/lEVs accelerate lung metastasis in mice bearing mammary tumors.